Hazard Assessment of LNG Loading-Unloading Process in Cirebon Port - Hary Devianto; Pramujo Widiatmoko; Isdiriayani Nurdin; Mitra Eviani (Dept. of Chemical Engineering, Diponegoro University, 2018)
Cirebon Port has spacious work and water area that provides opportunities to be developed in industrial sectors, particularly the petrochemical industries such as ethylene and Liquefied Natural Gas (LNG). In atmospheric condition, they are classified as volatile gas. Either in processing or transporting, they are stored in closed system. However, they still have a probability to be released to the environment and may lead to a fire or explosion. This probability is increased in the existence of coal stockpile in the port area which can evoke a fire. Therefore, a safety study is needed to identify the risk of the loading-unloading activities. The problem was solved by following steps. First, the data such as physical properties, layout area, and geographical condition around the port were collected. Then, the hazardous nodes were identified qualitatively, and then the quantitative analysis was done using As Low As Reasonably Practicable (ALARP) analysis. From the safety study, a suitable handling and safety system is provided to ensure safety viability in the ethylene and LNG loading-unloading process at the Cirebon port.Keywords: ethylene; hazard assessment; LNG; loading-unloading process; Quantitative Risk Assessment (QRA)